Back Cover: A Multifunctional Magnetic Material under Pressure (Chem. Eur. J. 26/2014). Issue 26 (23rd June 2014) - Rodríguez‐Velamazán, J. Alberto; Fabelo, Oscar; Beavers, Christine M.; Natividad, Eva; Evangelisti, Marco; Roubeau, Olivier
<x xml:space="preserve">Abstract</x> A multi‐technique study allowed the determination of the antiferromagnetic structure of [Fe(Metz)6](FeBr4)2 (Metz=1‐methyltetrazole), a unique and multifunctional magnetic material that combines spin‐crossover and long‐range magnetic order. The application of pressure modulates these types of magnetic order. For more information, see the Full Paper of J. A. Rodríguez‐Velamazán, O. Roubeau et al. on page 7956 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>